China’s LGBT Community: History, Current Situation and Future Prospects - Zhao, Ziqi (International Journal of Social Sciences and Public Administration, 2024)
The LGBT (lesbian, gay, bisexual, transgender) community in China has experienced a complex transition from secrecy to gradual openness. With social progress and changes in the international environment, the rights and social status of the LGBT community in China are also evolving. This article will explore the historical background, current social status, legal environment, and future prospects of the LGBT community in China, aiming to provide a comprehensive perspective on the development of the Chinese LGBT community.